A feasibility study of establishing fiscal council in Indonesia - Haryo Kuncoro (Universitas Islam Indonesia, 2018)
In this paper we address the quantitative measurement of credibility in fiscal policy in the case of Indonesia over the period 2001-2016. This preliminary paper focuses on the deviations of the actual budget balances from the projections about these balances in the preceding years. The objective is to extract from these data insights into the credibility of the government fiscal policies. We found that fiscal policy as conducted by government is not perceived as credible. The targets set forward by government are often not met and usually the divergence is on the negative side. Revenue and spending are overestimated, leading to a deficit bias and growing indebtedness of government. Those results suggest feasibility to establish the fiscal council with independent powers to conduct the credible fiscal policy in order to maintain fiscal sustainability in the long-term.